Research on optimization of indoor positioning batch ranging system based on DS-TWR algorithm - Hongwei SUN; Xuehong CAO; Liangbao JIAO; Lin MENG; Ziheng LIU; Feng YUAN (Dianxin kexue)
Aiming at the current problems of the ultra wide band (UWB) indoor positioning system based on the double sided two-way ranging (DS-TWR) algorithm, there are more communication times and a higher conflict rate in a multi-tag environment, an improved algorithm was proposed.The Hash algorithm to hash and distribute the communication content between the tag and the anchor was used, so that the anchor could reply to multiple tags in a regular and unified manner during each ranging process, which greatly reduced the number of times the anchor sends RES (responds) data.Experimental results show that the improved algorithms’ communication times between a tag and the anchor were reduced by 15% compared with the traditional DS-TWR algorithm, which increases the time proportion of the anchor receiving state in ranging, thereby reducing the anchor receiving RNG (range) data.The collision rate of packets, the success rate of ranging has increased by 43.6%.Due to the reduction in the number of communications required in each positioning cycle and the reduction in the collision rate between data packets, a smaller channel capacity would be required, thereby increasing the label capacity of the positioning system, which has strong engineering significance.